Use of a Virtual Mock Loop model to evaluate a new left ventricular assist device for transapical insertion. Issue 10 (October 2020) - Kado, Yuichiro; Smith, William A; Miyamoto, Takuma; Adams, Joseph; Polakowski, Anthony R; Dessoffy, Raymond; Horvath, David J; Fukamachi, Kiyotaka; Karimov, Jamshid H
We are developing a novel type of miniaturized left ventricular assist device that is configured for transapical insertion. The aim of this study was to assess the performance and function of a new pump by using a Virtual Mock Loop system for device characterization and mapping. The results, such as pressure-flow performance curves, from pump testing in a physical mock circulatory loop were used to analyze its function as a left ventricular assist device. The Virtual Mock Loop system was programmed to mimic the normal heart condition, systolic heart failure, diastolic heart failure, and both systolic and diastolic heart failure, and to provide hemodynamic pressure values before and after the activation of several left ventricular assist device pump speeds (12, 000, 14, 000, and 16, 000 r/min). With pump support, systemic flow and mean aortic pressure increased, and mean left atrial pressure and pulmonary artery pressure decreased for all heart conditions. Regarding high pump-speed support, the systemic flow, aortic pressure, left atrial pressure, and pulmonary artery pressure returned to the level of the normal heart condition. Based on the test results from the Virtual Mock Loop system, the new left ventricular assist device for transapical insertion may be able to ease the symptoms of patients with various types of heart failure. The Virtual Mock Loop system could be helpful to assess pump performance before in vitro bench testing.